Work inequalities in the crisis : (Revised edition 2011). - Vaughan-Whitehead, Daniel (International Labour Office, 2011)
Since the successive crises erupted, the increase in inequality has not been addressed. This important publication offers a comprehensive overview of recent developments in the workplace. It will help to promote a different policy agenda that is desperately needed to overcome the causes and consequences of the crisis, namely addressing work inequalities.' -Philippe Pochet, Catholic University of Louvain la Neuve, Belgium, and General Director of the European Trade Union Institute (ETUI), Brussels, Belgium.